HUBUNGAN ANTARA DAYA LEDAK OTOT LENGAN DAN KEKUATAN GENGGAMAN TANGAN DENGAN KEMAMPUAN SMASH DALAM PERMAINAN BULUTANGKIS PADA CLUB PB BINTANG GENERASI KOTA RAJA TAHUN 2018 - Lalu Muhammad Irwan; Dadang Warta Candra; Sri Erny Muliyani (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
The club PB. Bintang Generasi Kotaraja is still lacking in many players smash as caused by several things both in terms of technique and muscle.therefore, in the badminton smash punches in doing so has its own specification which punch is a punch over head smash that rely on the strength and speed of the arm and wrist in order to cock prod sharp dip towards the opponent. It needs to be proven through scientific studies in the form. With issues that have been proposed, then the purpose of this study was to determine whether or not relationship arm muscle explosive power and muscle strength hold hands with smash ability in the game of badminton at the club PB. Bintang Generasi Kotaraja in 2018.As for the formulation of research done in this study using metode product moment. The researchers axamined a population of 15 players, whith title Relationship arm muscle explosive power and muscle strength hold hands with smash ability in the game of badminton at the club PB. Bintang Generasi Kotaraja in 2018. The results of research and analysis done by using a statistical formula shows the results obtained from the t-value of 0,259 while t-table with a significant level of 5% ie 0,514, this shows that t-velue is smaller than t-table. So, then the alternative hypothesis (Ha) is rejected and the null hypothesis at this. Means so relationship arm muscle explosive power and muscle strength hold hands with smash ability in the game of badminton at the club PB.Bintang Generasi Kotaraja in 2018.